EVOLVING TRENDS IN THE CURRICULUM OF HIGHER LEVEL ISLAMIC EDUCATION IN KERALA: AN APPRAISAL FROM SOCIAL ENGAGEMENT PERSPECTIVE* - DR. SHAFEEQ HUSSAIN VAZHATHODI AL-HUDAWI (2013)
The main intention of this paper is to provide details on how Islamic Higher Education (IHE) and its curriculum evolved in Kerala. While doing this, the history of various educational organizations, their reform attempts will be dealt briefly, but with the main intention of tracing the evolution of curriculum. In the course of this, firstly, the paper provides a brief historical account of Islamic education at higher levels in India, but with specific focus on their curriculum. As obvious the central concern will be on the higher level IHE provided in various institutions throughout the breadth and length of Kerala. History of Islamic Religious Education (IRE) at primary and secondary levels, thus, is not specifically within the scope of the paper, unless such an account is demanded for explanation on the key purpose. The special focus of the paper will be on various current attempts of reform of the curriculum of these institutions, and what could be done further to make these institutions relevant to the empowerment of Muslims and their creative social involvements.